1977
DOI: 10.1128/jb.131.2.453-462.1977
|View full text |Cite
|
Sign up to set email alerts
|

Developmental-stage-dependent adenine transport in Neurospora crassa

Abstract: Although germinated conidia ofNeurospora crassa transport adenine through two different systems, only one of these, namely, the general purine transport system, which transports adenine, hypoxanthine, guanine, and 6-methylpurine, is present in freshly harvested conidia of the wild type. The second system develops during germination. The latter system can transport adenine and 6methylpurine. Time course and kinetic studies of adenine transport in freshly harvested conidia of an ad-8 mutant indicated that, in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
2

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
10
0
2
Order By: Relevance
“…Indirect evidence, through uptake measurements, also strongly suggests that nitrate, ammonium aspartate/glutamate and lactate transporters are induced/ activated early during germination (Magill & Magill, 1975; A. Apostolaki, C. Scazzocchio, V. Sophianopoulou, G. Diallinas, unpublished data). A similar developmental control of purine transporters has been detected by early studies in N. crassa (Pendyala & Wellman, 1977). Thus, unlike Saccharomyces cerevisiae, where highly specific sensor proteins can activate true transporters (Forsberg & Ljungdahl, 2001), A. nidulans and possibly other filamentous fungi might use their transporters per se for both sensing the environment and for the bulk transport of solutes.…”
Section: Regulation Of a Nidulans Purine Transporters During Conidiosupporting
confidence: 56%
“…Indirect evidence, through uptake measurements, also strongly suggests that nitrate, ammonium aspartate/glutamate and lactate transporters are induced/ activated early during germination (Magill & Magill, 1975; A. Apostolaki, C. Scazzocchio, V. Sophianopoulou, G. Diallinas, unpublished data). A similar developmental control of purine transporters has been detected by early studies in N. crassa (Pendyala & Wellman, 1977). Thus, unlike Saccharomyces cerevisiae, where highly specific sensor proteins can activate true transporters (Forsberg & Ljungdahl, 2001), A. nidulans and possibly other filamentous fungi might use their transporters per se for both sensing the environment and for the bulk transport of solutes.…”
Section: Regulation Of a Nidulans Purine Transporters During Conidiosupporting
confidence: 56%
“…However, the relation between transport and phosphoribosylation is not known in this organimn. In our experience, even short-term pulse-labeling studies of purine bases always yielded purine nucleotides in subsequent extractions of the cells (24,25). Sabina et al (29) found that an adenine-requiring mutant ofNeurospora (ad-8) not only could not transport hypoxanthine, but its hypoxanthine PRTase (EC 2.4.2.8; HPRTase) activity was very low.…”
mentioning
confidence: 76%
“…Uptake of purines and identification of intracellular purines. Procedures for the study of uptake of "4C-labeled bases, as well as for the separation and idenfification of labeled purine bases, nucleosides, and nucleotides have been previously described in detail (24,25). The same procedures were followed here without modification.…”
Section: Neurospora Strains and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two species also revealed differences in the level of the total RNA content during germination which remained unchanged with Dictyostelium (HAMER and COTTER 1983) but dropped sharply (30 min) and then increased again (45 min) with Neurospora (BRAMBL et al 1987). There are further interesting reports on regulatory aspects during spore germination which include the induction of an adenine transport system in Neurospora (PENDYALA and WELLMAN 1977), increased rates of germination by adenine and hypoxanthine in the case of Phytophthora infestans (CLARK and MELANSON 1978), transient increase of NADH and NADPH during germination oi Neurospora conidia (BRODY 1981), cAMP-induced phosphorylation of trehalase to overcome dormancy in yeast and Neurospora spores (THEVE-LEIN et al 1984) and the regulation of amidotransferase, the first enzyme in UDP-N-acetylglucosamine synthesis, by phosphorylation (ETCHEBEHERE and DA COSTA MAIA 1989). With a biotrophic fungi, the bean rust Uromyces phaseoli, cAMP-induced division and infection structure formation was reported (HOCH and STAPLES 1984).…”
mentioning
confidence: 99%